The Effect of Entrepreneurship Competency and Adaptability of Business Environment to Financial Performance of Small an Medium Business Units in Bima City - Nurul Huda; Aris Munandar; Syamsinirwani Syamsinirwani (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
The number of SMEs and the absorption of large manpower does not contribute greatly to the value of production and investment in the agro-industry sector and non-agro industry sector is a reflection of most SMEs in Bima city. This problem occurs because there are so many considerations of it, one of them is lack of competence of SMEs business sector, the limitations in the ability to adapt with the environment changes including market of innovation, access to information and financing, the difficulty in the procurement of capital and cheap, the limitations in innovation, technology changing that will affect all business performance of SMEs. The higher social competence (interaction, social relations, and social adaptation) owned by entrepreneurs, the greater financial success that entrepreneurs will achieve and improve business performance. The research method used is explanatory research by using a survey sampling approach. Conventionally, explanatory research is used to explain the relationship between variables through hypothesis testing. Then, the questionnaires will be distributed 156 SMEs in Bima city where the questionnaire have tested the validity and reliability then processed by using SPSS so that the accuracy of analytical tools can be reliable. The long-term goal to be achieved is increasing the competitive advantage and performance of SMEs throughout Bima city. The specific targets of this research are the enhancement of competitive advantage and performance of SMEs in Bima city with the entrepreneurial competence that is able to build business network and assimilate to external environment changes that encourage the efficient use of resources, improving the ability to build business networks, multiple sources of economic growth, create employment, networking in collaboration with business partners and enhancement of competitiveness, a better service for  clients and customers are need to be improved where they are not dependent on imported products that undermine the society economic tenacity, the ability to express themselves in constructing social relationship. The results of the t-test statistic for the obtained variable are t-count of 5.964 with a t-table value of 1.645 (5.964 ˃ 1.661) with a significance value of 0.000 less than 0.05 (0.000 < 0.05), the hypothesis that "Entrepreneurship competency influences SME financial performance in Bima City”. The results of the t-test statistic for the obtained variable are t-count of 0.373 with a t-table value of 1.645 (0.373 < 1.645) with a significance value of 0.710 greater than 0.05 (0.710 ˃ 0.05), hence the hypothesis that "Environmental Adaptability Business influences the financial performance of SMEs in Bima city.